Peningkatan ketahanan oksidasi karet alam melalui pengikatan antioksidan 4-aminodifenilamina secara kimia - Handayani, Hani; Maspanger, Dadi R.; Radiman, Cynthia L (Center for Leather, Rubber, and Plastic Ministry of Industry, Indonesia, 2016)
Natural rubber is very important in supporting the Indonesian economy from non-oil sector. However, natural rubber is not resistant to oxidation. Various attempts have been made to overcome the weaknesses; one of them is the addition of antioxidants as additives in the manufacture of rubber goods. However, it has the disadvantage of mechanical technique, including antioxidant blooming, resulting in failed products and decrease in antioxidants ability. The aim of this research is to improve the resistance of natural rubber from oxidation through the chemically-bound antioxidant into epoxidized latex. Fresh latex was deproteinized using 0.06 phr papain. Latex was epoxidized using formic acid and hydrogen peroxide at 70°C with stirring speed of 700 rpm for 3 hours. Then the 4-Aminodiphenylamine (4-ADPA) antioxidant was added with three variations mole percent of 4-ADPA between 0.025 to 0.1 mol/100 grams of rubber, and four variations in temperature were applied (between 27-80°C). The results showed that the optimum condition for the binding was at 27°C at a dose of antioxidants as much as 0.1 mol/100 grams of rubber. The analysis of FTIR spectra revealed that the binding of 4-ADPA into the epoxidized latex was as much as 1.93 phr. The Rheometer curve analysis showed that the natural rubber bound 4-ADPA was more resistant to ageing based on the value of R300.Keywords: latex, antioxidant, epoxidation, 4-ADPA, natural rubber oxidation.